Faktor-Faktor yang Berhubungan dengan Perilaku Mahasiswi dalam Penggunaan dan Pengelolaan Pembalut Wanita Berdasarkan Konsep PHBS di Sekolah Tinggi Meteorologi Klimatologi dan Geofisika Tangerang dalam Perspektif Promosi Kesehatan - mardika, alyanda_sahira; Rajab, Wahyudin; Safrudin, Safrudin (Jurnal Promosi Kesehatan Poltekkes Bengkulu, 2025)
The behavior of using and managing sanitary pads is a part of personal hygiene that relates to an individual's efforts to maintain cleanliness of the genital area during menstruation. This study aims to identify the factors that are associated with female students' behavior in the use and management of sanitary pads based on the Clean and Healthy Behavior (PHBS) concept at STMKG Tangerang from a health promotion perspective. This research uses a quantitative method with an analytical survey design and a cross-sectional approach. A total of 118 female students aged 16–25 years were selected using stratified sampling based on study programs. Data was collected using a questionnaire and analyzed using Chi-square testing. The results show a significant relationship between personal hygiene, environmental cleanliness, availability of facilities, and parental support with the behavior of using and managing sanitary pads (p-value < 0.05). The conclusion of this study is that female students' behavior in maintaining menstrual hygiene is associated with several factors that can be improved through continuous education and health promotion.